Fotossíntese em folhas e frutos do mamoeiro (Carica papaya I.) cv. Golden - Duarte, Maisa Melo (2011)
Papaya (Carica papaya L.) plant is susceptible to environmental changes that demand answers, physiological characteristics and reproductive during its development. Because it is of great economic importance to the state of Espirito Santo, studies on the effects of environmental stress in this species are essential to ensure better production and fruit quality. In order to know the effect of environmental stresses on the photochemical performance of papaya were analyzed with the chlorophyll a fluorescence transient in leaves and epicarp of the fruit during its development. The growth and photosynthetic activity were also monitored in leaves during the vegetative stage. The growth of papaya showed remarkable differences in canopy architecture and leaf number between the vegetative and reproductive stages. A higher stomatal conductance (gs) and carbon assimilation rate (A) increased to 30 days after planting (DAP), during which there was an increase in precipitation. Also, 150 DAP, fruiting period and increased demand for assimilates, we observed a higher rate of A. A smaller leaf photochemical performance was evidenced by the kinetics of chlorophyll fluorescence, at planting and at 30 and 90 DAP, but this same period, A and gs were high. At the beginning of fruit development (0-35 days), the specific flow of dissipated energy (DI0/RC) was high, suggesting an adaptive strategy while the fruits are perpendicular to the vertical axis of the plant. The photochemical performance total (PITOTAL) was higher in leaves than in fruits, due to the higher density of active reaction centers (RC / ABS) and the best performance of the redox reactions of photosystem I [dR0 / (1-dR0) ]. The results suggest that the epicarp of the fruits, unlike leaves, the photosynthetic apparatus has an important protective function, since the beginning of its development dissipate excess incident energy, thus maintaining the quality of the fruit